Security interests under english law, Civil code of Ukraine and draft Civil code of Ukraine - Chanysheva, Alina Rashydivna; Чанишева, Аліна Рашидівна (Одеса : Фенікс, 2026)
The law of England and Wales has served as source of inspiration for various legal systems. It has, arguably, affect Ukrainian private law law-making in the past. However, in terms of legal regulation of security interests, it seems that the 2026 draft Civil Code N14394 does not move Ukrainian law towards the English model in any strong institutional sense. Instead, it makes Ukrainian law more internally systematic and more classically civilian. The current Civil Code groups together a mixed list of devices securing performance of obligations, including trust ownership. The draft separates the general law of security interests from a narrower category of proprietary security rights and, within that category, recognises only pledge and retention. English law, by contrast, remains uncodified and device-based, with security interests structured around the mortgage, fixed charge, floating charge, pledge, and lien rather than around a single civil-code taxonomy.
Chanysheva A. R. Security interests under english law, Civil code of Ukraine and draft Civil code of Ukraine. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) / заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 2. С. 72-75. URL: https://doi.org/10.32837/11300.32972
Keywords: зобов’язання; засоби забезпечення виконання зобов’язання; порука; ци- вільне законодавство України; право довірчої власності; obligations; security interests; suretyship; civil legislation of Ukraine; trust ownership